Skolelukninger i Kommunalreformens skygge? En analyse af Kommunalreformens policy-konsekvenser - Bækgaard, Martin (Politik, 2010)
The article explores the e ects of the 2007 amalgamations of Danish municipalities on the policy area of public schools. Proponents of the municipal amalgamations argued that new municipalities, due to economies of scale, would be able to harvest economic gains by closing some of their existing schools in order to create bigger and more efficient units. Based on a data set containing information about all public schools in the school year 2005/2006, and whether they still existed in the school year 2008/2009, the analyses show that the reform did not have the intended effects as the number of school closures increased less in the new municipalities than in those municipalities that were left unchanged. The findings suggest that the municipal amalgamations introduced a geographical cleavage in new municipalities and that this cleavage has made it more diffcult to close public schools, as closures would cause considerable conflict.